Massive Splenic Rupture – An Unusual Presentation - Seetahal Shiva (Journal of Spleen And Liver Research, 2016)
A case report of massive splenic rupture with atypical presentation. It covers diagnostic work‑up, stabilization, and operative decision‑making.
Keywords: chronic cough